Framing Attention in Japanese and American Comics: Cross-Cultural Differences in Attentional Structure - Cohn, Neil; Taylor-Weiner, Amaro; Grossman, Suzanne (Frontiers in Psychology, 2012)
Research on visual attention has shown that Americans tend to focus more on focal objects of a scene while Asians attend to the surrounding environment. The panels of comic books— the narrative frames in sequential images—highlight aspects of a scene comparably to how attention becomes focused on parts of a spatial array. Thus, we compared panels from American and Japanese comics to explore cross-cultural cognition beyond behavioral experimentation by looking at the expressive mediums produced by individuals from these cultures. This study compared the panels of two genres of American comics (Independent and Mainstream comics) with mainstream Japanese “manga” to examine how different cultures and genres direct attention through the framing of figures and scenes in comic panels. Both genres of American comics focused on whole scenes as much as individual characters, while Japanese manga individuated characters and parts of scenes. We argue that this framing of space from American and Japanese comic books simulate a viewer’s integration of a visual scene, and is consistent with the research showing cross-cultural differences in the direction of attention.